Perceived effectiveness of whistleblowing in detection of fraud in Kenyan Football Clubs: moderated by ethical climate - Orwa, C. (Strathmore University, 2025)
Fraud in sports organisations undermines financial stability, integrity and public trust. In the Kenyan football Premier League, governance challenges including fraud, financial mismanagement and corruption continue to pose significant risks. Whistleblowing is a globally recognised tool for uncovering fraud, but its implementation and effectiveness within the Kenyan Football Premier League clubs remain underexplored. This study’s primary objective was to assess the effectiveness of whistleblowing systems on the detection of fraud in Kenyan Premier League Football Clubs. The specific objectives include: to examine the influence of the attributes of whistleblowing systems and to determine the influence of management perceptions towards whistleblowing on the detection of fraud in Kenyan Football Clubs. Additionally, the study sought to establish the moderating effect of ethical climate on the relationship between whistleblowing systems and the detection of fraud in Kenya. The study was underpinned by the Fraud Diamond Theory and the Machiavellianism Theory. It applied a pragmatism research philosophy along with a mixed methods research design. The target population was all the 18 football clubs in the Kenyan Premier League. A sample of 464 respondents was selected purposively. Primary data was collected using both closed and open-ended questionnaires. Descriptive and inferential statistical analyses were conducted using the Statistical Package for Social Sciences. The results were then presented using graphs and tables. The Pearson Correlation analysis indicated that all the predictor variables were positively and significantly correlated with the outcome variable. The predictor with the strongest association with the outcome variable was Attributes of Whistleblowing Systems followed by Management Perceptions Towards Whistleblowing. Additionally, Ethical Climate was found to have a positive and significant moderating role on the relationship between Whistleblowing Systems and Detection of Fraud. There are both significant and statistically significant relationships between the predictor variables and the outcome variable according to the regression analysis. The Beta Coefficient analysis showed that the Ethical Climate was the most critical determinant of Detection of Fraud, followed by Attributes of Whistleblowing Systems, and Management Perceptions Towards Whistleblowing, respectively. The study recommends that the Kenya Football federation should create clear rules to protect whistleblowers. These rules should allow football stakeholders to report wrongdoings anonymously and should protect them from being punished for speaking up. To make sure the rules are fair and accepted, the federation should involve different people in football like club officials, players and referees, when creating them. The federation should also take a strong stand against fraud by introducing tough penalties to stop dishonest behaviour in these clubs.
Full - text thesis